Harnessing the Power of the Internet: Developing Courseware Using Dynamic HTML and Multimedia Applications - Fryer, Colin (Proceedings of the International Conference on Networked Learning, 1998)
Dynamic HTML (DHTML) is an emerging Web standard that revolutionises how Web authors add interactive dynamic features to their Web pages. At the same time, DHTML relieves a Web server's load by shifting the processing demands for animation, data processing, and other interactive features to the client machine. The advent of DHTML has provided the infrastructure for Web pages to go beyond static text, images, and hyperlinks and become truly dynamic. Unlike previous multimedia technologies that required complex plugins or Java applets, DHTML capabilities are built into the next generation of 4.0 browsers. These technologies, however, while providing an implementation toolset for dynamic interactivity, do not provide a high level interface such as chat implicit in HTML and its authoring software. If the benefits of DHTML are to be enjoyed by the wider community of Web Designers and not to a small subset of programmers, there needs to be a fusion of DHTML using JavaScript coding, and the application of more accessible multimedia software through the use of plugin technology. The benefits of dynamic courseware are many. Information can be presented in a more compelling manner, interfaces can be more responsive and easier to use, and new types of applications previously found only on CD-ROMS are made possible.